Contribui????o previdenci??ria patronal e as verbas de natureza indenizat??ria - Silva, Thiago Perez Rodrigues da (2016)
This work has the scope to analyze the employers' social security contributions and their impact on the amounts credited to the employees which they discuss their nature, especially whether these incomes have damages or remunerative nature. Therefore, the work discusses the national tax system, discussing the concept of tribute and their species, with special emphasis on the contributions. Further it, discusses the tax on the payroll, analyzing the taxes levied on such basis and mapping an analysis of such a tax. Then proceeds to analyze the labor amounts paid to workers recurrently discussed before the Judiciary, which are the untaken holiday and its additional 1/3, 15 days before the sickness, notice indemnified, maternity pay, salary paternity, night, risk premium, overtime indicating legislation, doctrine and cases law in order to demonstrate the understanding of the nature of such incomes and their effects on taxable basis of the social contribution to proper social security levied on the employers, along the lines of article 150, I, of the Federal Constitution and article 22, of Federal Law n?? 8.212 /1990.